Pengaruh Sertifikasi Halal dan Kompetensi Kewirausahaan terhadap Kinerja UMKM dengan Kepercayaan Konsumen sebagai Variabel Mediasi (Studi Kasus pada UMKM di Jakarta Timur) - Esa Putu Munggara; Aditya Pratama; Riswandi Riswandi (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the effect of halal certification and entrepreneurial competence on MSME performance with consumer trust as a mediating variable in MSMEs in East Jakarta participating in the empowerment program of the Ministry of MSMEs of the Republic of Indonesia. This study employed a quantitative approach with a purposive sampling technique involving 140 respondents. Data were analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM). The results indicate that entrepreneurial competence has a positive and significant effect on MSME performance, while halal certification and consumer trust have no significant effect on MSME performance. Halal certification and entrepreneurial competence are proven to have a positive and significant effect on consumer trust. Furthermore, consumer trust is unable to mediate the effect of either halal certification or entrepreneurial competence on MSME performance. These findings indicate that improvement in MSME performance is largely determined by the internal capabilities of business actors rather than consumer trust factors. Therefore, strengthening entrepreneurial competence needs to be the main focus in MSME development programs, while halal certification plays a greater role in enhancing business credibility and image.